Why Don't We Have a Vaccine Against……….? Part 2. Bacteria. Issue 2 (March 2016) - Rosenthal, Kenneth S.; Kuntz, Aaron; Sikon, Joseph
Abstract : Abstract: Despite the large number of vaccines, this review asks the question: why do we not have vaccines for all infectious diseases? The first of this series discussed basics of vaccine immunology, new approaches, and outlined some of the difficulties and approaches that are being taken for antiviral vaccines. The second part of the series focuses on antibacterial vaccines and the approaches that are being taken to develop vaccines for some of the most important bacteria.